إنشاء تطبيق ضمن بيئة نظم المعلومات الجغرافية لتثقيل الطرقات بالمعالم السياحية - عباس إياد; شعبان فادي; إبراهيم سليم (Latakia University Journal -Engineering Sciences Series, 2018)
ساهمت العلوم الحديثة في تحسين عمليات التحليل وفهم المستقبل، وكلما كانت المعرفة والمعلومات متوفرة كلما كان التخطيط جيد، فالبيانات الأفضل تقود لقرار أفضل، وهذا هو أساس نظم المعلومات الجغرافية (GIS)، التي ساهمت منذ ظهورها في تذليل العقبات البحثية، نتيجةً لما تتمتع به من قدرة على معالجة وتحليل معلومات مكانية ضخمة ومتنوعة. تمثل نظم المعلومات الجغرافية (GIS) حقلاً هاماً في مجال التخطيط السياحي، لأنها تساهم في تطوير تطبيقات خاصة تخدم السياحة بمفهومها الحديث. في هذا البحث سيتم استخدام نظم المعلومات الجغرافية (GIS) لبناء نظام فعال يحسن التخطيط السياحي في محافظة اللاذقية بدءاً من بناء قاعدة بيانات تحتوي على المعالم المرتبطة بالعملية السياحية من مطاعم وفنادق ومعالم دينية وأثرية... وإدخال تقييم كل معلم، ومن ثم إنشاء أداة جديدة ضمن بيئة نظم المعلومات الجغرافية توظف المعالم السابقة في تثقيل شبكة الطرقات ضمن المحافظة من الناحية السياحية، أي تحديد الوزن السياحي لكل مسار من شبكة الطرق. New sciences have greatly contributed in improving analysis processes and subsequently lead to better understanding of the future. The more knowledge and information are available, the better planning process will be. Furthermore, better data leads to better decision-making. This is the basis of Geographic Information System (GIS). Due to its great ability in processing and analyzing extensive and various amount of spatial data, GIS has solved many obstacles in the research field since it was first launched. GIS plays an important role in the field of tourism planning as it contributes in developing new applications that serve modern touristic. In this research paper, GIS will be used to build an effective system that will improve touristic planning in Lattakia governorate. A spatial database will be created, that includes the most prominent touristic places in the city, such as restaurants, hotels, religious and historical sites.etc. Each of the touristic attractions will be evaluated, and then a tool , created in GIS environment, will be used for weighting roads network, in order to determine the touristic weight for each path in roads network.